REVIEW : ANALISIS PEREDARAN PENGGUNAAN PENGAWET LEGAL DAN ILEGAL YANG DIGUNAKAN PADA PRODUK PANGAN - Faizal Auladi Rivianto; Fitri Aida; Febry Nola; Nadia Andriani; Marsah Rahmawati Utami; Lina Nurfadhila (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Food Additives (BTP) are ingredients added to food to change the nature, texture, taste, and shape of a food product. Food Additives include preservatives, colorings, flavor enhancers, and thickeners, either having nutritional value or not having nutritional value. Preservative BTP is a food additive that prevents or inhibits fermentation, acidification, or other decomposition of food caused by microorganisms. Preservatives in food are divided into 2: legal preservatives (allowed at certain levels) and illegal (not allowed to be used). Types of legal preservatives include BHT, sorbic acid, sodium benzoate, potassium sorbate, sulfite, and sodium nitrite. In contrast, illegal preservatives include formalin, potassium bromate, salicylic acid, diethylpyrocarbonate, dulsin, and potassium chlorate. This study aims to determine the use of preservatives that are widely used in the market, both legal and illegal. The method used is a literature review. The results obtained are the use of illegal preservatives such as borax and formalin, which are still widely found in the market, and for legal preservatives commonly used, sodium benzoate, benzoic acid, potassium sorbate, sulfite, and sodium nitrite. However, some legal preservatives are still found to exceed the maximum usage limit.